From Place Attachment to Kinetic Epiphany: A Tuanian Reading of Stevens’ Journey in The Remains of the Day - Huang, Rucheng; Song, Qijun (Cultural Arts Research and Development, 2025)
This study examines Kazuo Ishiguro’s The Remains of the Day through the theoretical framework of humanist geography, specifically employing Yi-Fu Tuan’s theories of place and space. While prior scholarship has predominantly explored the novel through narratological and cultural perspectives, a significant lacuna exists in spatial analyses concerning the interplay between Stevens’s self-deception and his spatial practices. This study addresses this gap by demonstrating how Stevens’s self-deception is both sustained and ultimately disrupted through his engagement with the novel’s spatial configurations. The study finds that Stevens’s deep attachment to the symbolic location of Darlington Hall underpins his sustained performance of dignity and loyalty, thereby reinforcing his self-deception. In contrast, his journey through the English countryside transforms abstract spatial concepts into tangible sites that provoke introspection and challenge his constructed identity. This analysis transcends metaphorical interpretations of space, offering a novel perspective on the psychological and environmental dimensions of self-deception. Through a close reading of the novel’s geographical portrayals, this study contributes a novel perspective to the existing literature, elucidating how Stevens sustains his self-deception through spatial practices and the subsequent collapse of his self-deception during his mobility. This analysis enriches our understanding of the psychological and environmental dimensions of self-deception in The Remains of the Day.